(untitled) (Experimental biology, 2015)
In 2008, fisheries and aquaculture to FAO data set on the world market for about 142million tons of fish. The main obstacle to increasing the productivity of aquaculture are bacterial diseases of fish, particularly common in closed basins or ponds. Traditional methods for dealing with such problems, such as antibiotics, to date, are not effective, due to the widespread dissemination of antibiotic resistance. An alternative solution to this problem may become probiotic preparations.